Novel CMOS image sensor pixel to improve charge transfer speed and efficiency by overlapping gate and temporary storage diffusing node - Yang, Cui; Peng, Guo-Liang; Mao, Wei; Zheng, Xue-Feng; Wang, Chong; Zhang, Jin-Cheng; Hao, Yue (Chinese physics B, 2021)
A novel CMOS image sensor (CIS) pinned photodiode (PPD) pixel, named as O-T pixel, is proposed and investigated by TCAD simulations. Compared with the conventional PPD pixel, the proposed pixel features the overlapping gate (OG) and the temporary storage diffusing (TSD) region, based on which the several-nanosecond-level charge transfer could be achieved and the complete charge transfer from the PPD to the floating node (FD) could be realized. And systematic analyses of the influence of the doping conditions of the proposed processes, the OG length, and the photodiode length on the transfer performances of the proposed pixel are conducted. Optimized simulation results show that the total charge transfer time could reach about 5.862 ns from the photodiode to the sensed node and the corresponding charge transfer efficiency could reach as high as 99.995% in the proposed pixel with 10 μm long photodiode and 2.22 μm long OG. These results demonstrate a great potential of the proposed pixel in high-speed applications.